Customer switching behavior analysis in telecommunications via mobile number portability - Sanisoğlu, Meltem (Fen Bilimleri Enstitüsü, 2017)
The mobile telecomunications industry in Turkey has experienced several innovations that changed the market dynamics by increasing the competition among mobile service providers. As one of these innovations, Mobile Number Portability (MNP) has been introduced in Turkey in 2008. Since the implementation, it has become more important for mobile telecommunication companies to maintain existing customers as well as acquiring new customers. As MNP leads to customers' switching behavior; the relationship among them has been broadly studied in the literature. This thesis examines the determinants that has been analyzed for influencing customers switching behavior in the previous studies which are service quality factors, customer satisfaction, switching barriers and switching facilitators. The main purposes of this study are exploring differences between mobile phone service users in terms of their switching decision to another service provider in Turkey via MNP. To identify switchers and non-switchers and to findout differences between heavy and light switchers; exploratory factor analysis and discriminant analysis were performed to analyze the data from Turkish mobile phone users which have knowledge about MNP concept. Further, regression analysis was applied to understand the driving factors that have impact on customers' intention to switch. The analyses highlight that the network quality is the most important factor that discriminates switchers from non-switchers among Turkish mobile service customers. The findings also revealed that customers who switch one-time and customers who switch multiple times differ from each other with customer support and quality of retail stores perception. Customers who switched only once attach more importance to customer support quality, whereas customers who switched more than once give more importance to the quality of mobile service providers' retail stores. Further, it is also exhibited that customer satisfaction, attractiveness of alternatives, loss cost, gender, billing accuracy and network quality are the major factors that best explain customers' intention to swith via MNP. The findings can be utilized by mobile services provider companies for developing and implementing customer acquisition and retention strategies. For future research, it is suggested to examine the effect of switching factors on customers switching intention in more detailed way, including several other variables and countries and engage in comparative analyses; in order to explore cultural charasteristics' influence on switching intention and behavior as well.
Mobil numara taşıma yolu ile operatör değiştirme davranışlarının analizi
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2017
Keywords: mobile telecomunication; mobil telekomünikasyon; mobile phones